Pengaruh risiko usaha terhadap rasio kecukupan modal inti (TIER 1) pada bank-bank kelompok buku 3 dan buku 4 - Adi Isa Ansori; Herizon Herizon (STIE Perbanas Surabaya, 2017)
This study tried to determine the effect of liquidity risk measured by LDR and IPR, Credit risk measured by APB and NPL, market risk measured by IRR and PDN, operational risk measured by BOPO, and FBIR both simultaneously or partially. On Core CAR (TIER 1) in Bank group of book 3 and book 4. The sample was selected using purposive sampling technique, consisting of five banks such as PT Bank Negara Indonesia, PT Bank Maybank Indonesia, PT Bank Tabungan Negara, PT Pan Indonesia Bank, and PT Bank Permata. The secondary data were taken from published financial statements starting from first quarter 2010 until second quarter 2015. They were collected by documentation method and analyzed using linear analysis. The result shows that, partially, LDR, IPR, NPL, PDN, BOPO and FBIR have significant effect on Core CAR (TIER 1). Simultaneously, LDR, IPR, APB, NPL, IRR, PDN, BOPO, and FBIR, as represented by liquidity risk, credit risk, market risk, and operational risk partially have significant effect on Core CAR (TIER 1) in Bank group of book 3 and book 4.